ANALISA PERCEPATAN PROYEK METODE CRASH PROGRAM STUDI KASUS: PROYEK PEMBANGUNAN GEDUNG MIXED USE SENTRALAND - Restu Rama Bayu Adi; Devinta Elga Traulia; M. Agung Wibowo; Frida Kistiani (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2016)
When the implementation of construction projects, there are several barriers that are often experienced and can cause delays. According to Presidential Decree No. 54 of 2010 delays can incur a penalty of 1/1000 of the contract price. Delays can be taken to help accelerate the work. Scheduling a project conceived for the target specified time can be achieved. Scheduling has a series of activities related and have a total duration of the longest (critical path). Crash program is a way to accelerate the estimated costs required to reduce the time work on the critical path. Calculation begins with finding the critical path then perform crashing to obtain cost slope. Mixed Use Building Project Sentraland delayed, the author wants to analyze the time and cost of accelerating the work with method of program crashes. The normal duration for the structure 7 to Floor Roof Floor Level (Floor RL) is 203 days, at a cost of Rp 36,718,664,136. The acceleration process is divided into three (3) scenarios. Scenario 1 Job Fields with crashing duration of 191 days and costs Rp 36,907,386,256, Scenario 2 Plates Works Floor and Beam with a duration of 188 days and costs Rp 37,759,094,653, Scenario 3 Employment Column, Plates Floor and Beam with a duration of 176 days and cost Rp 37,930,808,077. Of the value of cost slope and a graph of cost and time, acceleration is obtained optimum point Scenario 1